Evaluation of Cement Mortars incorporating Calcined Red Mud: Characterisation and Strength Development - Pavia, Sara (Springer, 2026)
Transforming red mud, a waste product from aluminum production, into a valuable resource for construction industry offers manifold benefits: managing hazardous waste stockpiles, promoting sustainability in the building sector by decreasing cement consumption, environmental remediation. Red mud, a byproduct from the ALCOA San Ciprián industrial complex in Lugo, Spain, was subjected to calcination at two different temperatures. This process was conducted to enhance its reactivity, with the goal of utilizing it as a partial cement replacement in mortars. This study investigates the strength development of these mortars, considering two key variables: the substitution rate of red mud (fixed at 15% by weight of cement) and the calcination temperature of red mud (tested at both 300°C and 600°C). The investigated mortars are characterized using thermogravimetric and differential thermal analysis and X-ray diffraction techniques to provide valuable insights into their composition and properties. The results indicate that calcination induces changes in the crystalline structure of red mud; the phase transformation in calcined red mud involves conversion of mineral compounds like goethite to hematite, which results in more reactive red mud. The evolution of mortar strength is analysed in relation to the presence and proportions of crystalline phases within the mortars. These phases are examined as a function of three key factors: the temperature at which calcination occurs, and the duration of the curing process. This study also conducts an initial exploration into evaluating the photocatalytic potential of red mud for its possible use as a photocatalyst in cement-based materials. Transforming red mud, a waste product from aluminum production, into a valuable resource for construction industry offers manifold benefits: managing hazardous waste stockpiles, promoting sustainability in the building sector by decreasing cement consumption, environmental remediation.
Lecture Notes in Civil Engineering (LNCE, volume 743)
CEES 2025 Construction, Energy, Environment and Sustainability
PUBLISHED
Bari
Keywords: Calcined Red Mud; Photocatalytic Activity; Strength Development; Characterisation